Anthropometric and physical performance determinants of young tennis players progressing through a talent identification and development programme - Chapelle, L.; Pion, J.; Clarys, P.; Rommers, N.; D`Hondt, E. (International Journal of Sports Science & Coaching, 2023)
This study examined the influence of both anthropometric and physical performance determinants on the likelihood to be selected to progress through a talent identification and development programme in young tennis. Data were collected in 538 young tennis players (323 males and 215 females) from 6 age categories (U8-U13). A principal component analysis was used to generate one anthropometric determinant (based on body height, body weight and maturity offset) and four physical performance determinants: speed and agility (based on 5 m sprint, 20 m sprint and 505 change of direction test); jumping power (based on standing broad jump and standing broad jump in series); motor coordination (based on balancing backwards and jumping sideways) and tennis ball control (based on a throw and catch test and hold tennis ball up test). For all determinants, tertiles were generated for every age category and both sexes separately. Univariate binary logistic regressions were performed to examine the influence of each determinant on the chances to be selected to progress in the talent identification and development programme. Significant odds ratios were found for all included anthropometric and physical performance determinants (p < 0.05), ranging from 0.26 to 7.50 in the male young tennis players and from 0.18 to 6.87 in the female young tennis players. The included determinants influenced selection chances mostly in the early age categories (U8-U10) as opposed to the later age categories (U11-U13). Future research should examine the influence of additional determinants (such as tennis (match-play) performance) on the selection chances to progress through a talent identification and development programme.